Ad Hoc on-Demand Distance Vector (AODV) Routing Protocol Performance Evaluation on Hybrid Ad Hoc Network: Comparison of Result of Ns-2 Simulation and Implementation on Testbed using PDA - Sari, Riri Fitri; Syarif, Abdusy; Budiardjo, Bagio (UI Scholars Hub, 2008)
Ad Hoc on-Demand Distance Vector (AODV) Routing Protocol Performance Evaluation on Hybrid Ad Hoc Network: Comparison of Result of Ns-2 Simulation and Implementation on Testbed using PDA. In Mobile Ad hoc NETwork (MANET), node supplemented with wireless equipment has the capacity to manage and organise autonomously, without the presence of network infrastructures. Hybrid ad hoc network, enable several nodes to move freely (mobile) to create instant communication. Independent from infrastructure. They could access the Local Area Network (LAN) or the Internet. Functionalities of ad hoc network very much dependent on the routing protocol that determines the routing around node. Ad hoc On-demand Distance Vector (AODV) is one of routing protocols in ad hoc network which has a reactive characteristic. This protocol is the most common protocol being researched and used. In this Research, AODV protocol investigation was conducted by developing a testbed using Personal Computer, several Laptops (the Linux Red Hat operation system 9.0 and Fedora Core 2), and Personal Digital Assistant (PDA). This research also made a complete package by mean of cross compilation for PDA iPAQ. In general, results obtained from the simulation of AODV protocol using Network Simulator NS-2 are packet delivery ratio 99.89%, end-to-end delay of 0.14 seconds and routing overhead of 1,756.61 byte per second. Afterwards results from simulation were compared to results from testbed. Results obtained from testbed are as follows: the packet delivery ratio is 99.57%, the end-to-end delay is 1.004 seconds and the routing overhead is 1,360.36 byte per second.